TITLE: EFFECTIVE METHODS AND APPROACHES IN LEARNING THE GERMAN LANGUAGE (Modern education and development, 2025)
This article explores effective methods and approaches in learning the German language. It discusses the significance of language immersion, grammar-translation techniques, communicative practices, and the integration of digital tools. The paper aims to highlight how these strategies can enhance language acquisition, promote motivation, and develop all four language skills: reading, writing, listening, and speaking.